Effects of serum TSH and FT4 levels and the TSHR-Asp727Glu polymorphism on bone: the Rotterdam Study - Van Der Deure, Wendy M.; Uitterlinden, André G.; Hofman, Albert; Rivadeneira, Fernando; Pols, Huibert A. P.; Peeters, Robin P.; Visser, Theo J. (Clinical endocrinology (Oxford), 2008)
Summary Background  TSH and thyroid hormone may have independent effects on bone. In this study we investigated the association of TSH and free T4 (FT4) with different bone parameters in human subjects. TSH and FT4 are known to be associated with body mass index (BMI) and a higher BMI gives a higher bone mineral density (BMD). Thus, we aimed to determine whether the effects of TSH and FT4 on bone are mediated by BMI. As TSH exerts its biological effect through the TSH receptor (TSHR), the TSHR gene might be a candidate gene affecting bone mass. The TSHR‐Asp727Glu polymorphism is associated with lower TSH levels. We therefore examined the association of this polymorphism with bone parameters. Method  Genotypes were determined by Taqman assay in 4934 elderly Caucasian men and women of the Rotterdam Study, of whom BMD and bone geometry data were available. Serum thyroid parameters were available in a random set of 1327 subjects,. Results  Femoral neck BMD as well as narrow neck BMD and cortical thickness increased with serum TSH. However, FT4 was more strongly and negatively associated with bone parameters. Regression models showed BMI‐dependent and ‐independent effects of both TSH and FT4 on bone. Carriers of the TSHR‐Glu727 allele had a 2·3% higher femoral neck BMD. Conclusion  In line with the effect of TSH on bone in mice, serum TSH shows a positive trend with BMD in human subjects, a finding that is strengthened by the association between the TSHR‐Asp727Glu polymorphism and femoral neck BMD. However, serum FT4 has a much greater influence on bone than TSH.